Application of Bay‘ al-‘Inah in Islamic Banking and Finance: From the Viewpoint of Siyasah Shar‘iyyah - Nursyamsiah, Tita; Kayadibi, Saim (2012)
In siyasah shar‘iyyah perspective, the rulers have to administer shari‘ah principles to get beneficence (salah) and to prevent from any form of harm or corruption (fasad). Thus, any muamalah activities are allowed providing that no substantive shari‘ah principles are violated, including any activities in Islamic banking. Islamic banking products have enhanced their popularity since the last two decades, have taken more attention in sector of banking and financing due to its characteristics and differences compared with conventional bank and have been trusted as a solution for the current crisis as well. Many banks have created and adapted the system of Islamic Banking based on the shari‘ah principles which are the Quran and the Sunnah followed by the consensus of the jurists and interpreters of Islamic law. The main difference between Islamic Banking and its counterpart is particularly prohibition of riba. This main concept has deliberately led many scholars of Islamic law to explore the system of Islamic banking which must be set free from riba. Moreover, there is an aqd named bay al-‘inah that leaves any issues among the scholars. Bay‘ al-‘Inah refers to the selling of an asset by the bank to the customer through deferred payment. It comprises two agreements (akad). In the first agreement, the bank sells an identified asset to the customer at an agreed price. The customer can complete the purchase of bank’s asset via fixed monthly installments on agreed tenure. While for the second agreement, the bank re-purchases the same asset from the customer at a lower price. Upon completion of the 2nd transaction, the bank will pay the lump sum amount as agreed by both parties in the agreement. Some fuqaha have different opinion on this transaction, particularly that al-‘inah has inherent riba and is an unlawful transaction. Especially in Malaysia, bay al-‘inah has been offered though its application in Islamic banking which has left many issues particularly about the existence of riba and illegal transaction which violate shari‘ah itself. This study thus attempts to describe bay al-‘inah itself and analyzes the different thoughts among some scholars about bay al-‘inah in case of its implementations in Islamic banking system which will highlight the reality and tricky usage of it in Islamic banking and Finance issues. Keywords: Bay‘ al-‘Inah, Islamic banking system, Siyasah Shar‘iyyah; Riba.